Cambodia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cambodia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights 6.9 percent expected growth in Cambodia's economy in 2017, with moderating private investment offset by higher public spending and robust construction and tourism activities. Headline inflation rose to 3 percent in 2016 and 3.5 in the first half of 2017, driven mainly by higher food and energy prices. Overall credit growth has slowed, owing in part to policy measures. Real estate sector-related bank credit growth, however, remains strong, supported by demand for housing from Cambodia's young and growing middle-income population. Real GDP growth is projected to remain robust over the next few years.